Avia Saga: A Gamified Mobile-Based Learning Management System - Oswald, Putra Aldo; Gunawan, Dennis (Universitas Multimedia Nusantara, 2024)
The usage of Learning Management Systems (LMS) has increased since the Covid-19 pandemic. LMS have drawbacks despite the advantages they provide. To fully support the advantages they provide, students must be motivated and involved. Adding gamification to the LMS is one way to potentially solve this issue. The MDA framework and Octalysis are combined in this research's gamification approach. The application, named Avia Saga, was designed and built using Flutter and Spring Boot as a mobile application. A trial of the application was conducted with 38 students majoring in Informatics. The evaluation of the application was done using the Hedonic-Motivation System Adoption Model (HMSAM) with a Likert scale. The research results revealed a 7% increase in the behavioral intention to use category, suggesting a greater inclination for reusing the application, and an 11.7% increase in the immersion category, indicating elevated sentiments of users being carried away by the ambiance while using the application.